PENGELOLAAN OBJEK WISATA MASJID RAYA PEKANBARU SEBAGAI DESTINASI WISATA KOTA PEKANBARU - Yanto, Yopi; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Masjid Raya Pekanbaru Attraction is a very potential to become a leading tourist destination in the city of Pekanbaru, because the grand mosque is the oldest mosque in the city of Pekanbaru and one Heritage should be retained and managed as well developed. The problems faced by the Department of Culture and Tourism manage Masjid Raya Pekanbaru is budgeted funds at very minimal.This study aims to see how the Management Attractions Masjid Raya Pekanbaru as Travel Destinations Pekanbaru. Management Attractions Masjid Raya Pekanbaru Attraction so grand mosque became the city's main tourist destinations pekanbaruThis study uses qualitative research methods to examine the descriptive data. The concept of management theory. In collecting the data, researchers use interviewing techniques, observation, and documentation. By using key informants as a source of information and as a source triangulation techniques in testing validitation data.These results indicate that the Management Attractions Pekanbaru as the Masjid Raya Pekanbaru City Sightseeing was not optimal. This is evidenced planning, organizing, directing, and monitoring are not running properly. Then the inhibiting factors in the Management Attractions Masjid Raya Pekanbaru namely human resources that have not been professional, yet construction coordination with various agencies and also insufficient promotion. It is caused due to lack of support from the government of Pekanbaru. This making the grand mosque pengololaan less successful.Keywords: Management, Masjid Raya, Pekanbaru City Destination